The Feto-Maternal Outcomes and Incidence of Early-and Late-Onset Preeclampsia - Ayesha Naeem, Sadiq Jan, Muhammad Ali, Hafsa Mubashir, Sadia Hanif, Sughra Abbasi (Pakistan Journal of Medical & Health Sciences, 2022)
Hypertensive disorders in gestation are categorized as hypertension in pregnancy, chronic hypertension, eclampsia and pre-eclampsia. The World Health Organization states: “There are 529,000 maternal deaths annually worldwide due to pre-eclampsia and eclampsia. This study will help in determining pregnancy outcomes in early vs late-onset pr-eclampsia. Aim: To access the pregnancy outcomes of early and late onset pre-eclampsia. Study Design: A retrospective, descriptive and cross-sectional study Place and Duration: In the Obstetrics and Gynecology department of Allama Iqbal Memorial Teaching Hospital Sialkot and Islamic International Medical College, Rawalpindi for one-year duration form January 2021 to December 2021. Methods: A total 130 were admitted to the gynae ward with pre-diagnosis of pre-eclampsia were included. The cut-off value of the early and late onset PE was thirty-four weeks. Pre-eclampsia analysed < 34 weeks was labeled as early-onset pre-eclampsia and if diagnosed after 34 weeks will be labeled as late-onset pre-eclampsia. Obstetric and perinatal outcomes were assessed with version 21 of the Social Sciences Statistical Package. Results: A total 130 were admitted to the gynae ward with pre-diagnosis of pre-eclampsia were included. The severe pre-eclampsia was observed in 48(36.9%) pregnant women and 82 women (63.1%) had no symptoms of severe pre-eclampsia. In 38 (29.2%) cases; early-onset pre-eclampsia was detected and late-onset PE in 92 (70.7%) cases. The rate of severe PE in early-onset PE has been documented in 22 (57.8%) of 38 cases, and severe PE has been reported in late-onset PE in 29 (31.5%) of 92 cases. Adverse maternal outcomes occurred in 20 cases, including 7 cases of placenta abruptio and 3 cases of eclampsia with seizure disorders. Conclusions: The results indicate that in addition to intensive fetal monitoring in women with early-onset pre-eclampsia, attention should be paid to neurological, cardiopulmonary, and haematological parameters. Keywords: late onset, early onset; pregnancy outcome and preeclampsia.